Fenton Process for The Treatment of Wastewater Effluent from the Pharmaceutical Industry - Sarkale, Prajkta; Chougale, Sanjivani; Patil, Priyadarshani; Jadhav, Aasawari; Pathade, Girish (Journal of Neonatal Surgery, 2025)
The present study intends to investigate the performance of the Fenton process as one of the most efficient (AOPs) in a batch mode for treating wastewater effluent from the pharmaceutical industry, as well as the parameters that influence reaction such as pH, hydrogen peroxide (H2O2) and ferrous sulphate heptahydrate doses (FeSO47H2O) doses at various reaction times. Fenton process is low cost, highly efficient and eco-friendly technologies in the removal of organic pollutants in wastewater using hydroxyl radicals for oxidation. The obtained results indicated that the authenticated response to the chemical oxygen demand (COD) removal was 92-94 % at optimum values of pH, H2O2 dose, FeSO47H2O dose and reaction time, 3, 2 mL, 3 g and 60 min respectively. Under these conditions, the residual COD after Fenton oxidation process becomes 100 mg/L. Obtained results have shown that the process is effective for removal of COD and it can be applied for the treatment of pharmaceutical industry’s wastewater effluent